Teacher Roles in Fostering Learner Autonomy: Pre-service Teachers Practice in Pre-service Teaching Program - Siti Azhariah; Nenden Sri Lengkanawati; Rojab Siti Rodliyah (SALEE: Study of Applied Linguistics and English Education, 2023)
Learner autonomy has been introduced to English language teaching and learning for a very long time. Yet, there are many education practitioners who are not aware of this concept, pre-service teachers, or what we can call future teachers are not exceptions. This study was aimed to investigate pre-service teachers’ practice in fostering learner autonomy during pre-service teaching programs. A survey questionnaire was employed to 78 pre-service teachers majoring in the English Education Program at one University in Indonesia. The results showed that the pre-service teachers often played teachers’ roles in fostering learner autonomy during the pre-service teaching program. They played various roles such as manager and organizer, facilitator, counselor, and resource. The most played role was manager and organizer, meanwhile the least played role was facilitator.